Evaluation of the application of the principles of industrial sanitation and employee hygiene - Pamukti, Kevin Bagus; Juwitaningtyas, Titisari (Journal of Halal Science and Research, 2022)
The food industry is an industry that processes agricultural products into products, all of which are ready for consumption by a community. Therefore, the food industry is more involved in the downstream part of making these products. The primary function of the food industry is to save, disseminate, and increase the added value of agricultural products effectively and efficiently. Sanitation is an effort that monitors several environmental factors that affect humans and significantly impact the effect, damage to physical development, health, and survival in life, or efforts to maintain food, workplace, or free from pollution caused by bacteria, insects, or other animals. This study aims to analyze industrial sanitation and employee hygiene based on the reference in a Regulation of the Minister of Industry of the Republic of Indonesia No. 75/M-IND/PER/7/2010 concerning Good Processed Food Production Methods. The analytical method uses a check sheet, descriptive statistical analysis, and fishbone diagrams. The results of the analysis showed that the application of industrial sanitation and employee hygiene at Sweet Sundae was good, with the percentage of application is 85% being implemented and 15% not being implemented.